See, walk, and kick: Humanoid robots start to play soccer - Behnke, S. (International Journal of Computer Science in Sport, 2006)
Robotic soccer superseded chess as a challenge problem and benchmark for artificial intelligence research and poses many challenges for robotics. While simulated, wheeled, and four-legged robots have been playing soccer games for some years now, the RoboCup Humanoid League raised the bar again. This paper describes the mechanical and electrical design of the humanoid robots, which team NimbRo constructed for RoboCup 2006. The paper also covers the software used for perception, behavior control, communication, and simulation. Our robots performed well. The KidSize robots won the Penalty Kick and came in second the overall Best Humanoid ranking.